ANALYSIS OF THE IMPLEMENTATION OF LEARNING BASED ON QUR'ANIC VALUES IN FOSTERING SOCIAL ETHICS AT SCHOOL - Muharomah, Nuri Iza; Chotib, Moch; Supriadi, Supriadi (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
This study aims to analyze the implementation of Qur'anic values-based learning in fostering social ethics in schools. Qur'anic value-based learning becomes relevant amidst the challenges of globalization that often erodes moral values, especially among the younger generation. Using qualitative methods, this research explores how Qur'anic values are integrated into the curriculum, teaching methods and social interactions at school. It also discusses the role of teachers as facilitators and role models in instilling Qur'anic values such as honesty, responsibility, caring and tolerance. The results show that the Qur'anic value-based approach is able to shape the character of students who have a high awareness of social ethics, such as mutual respect, solidarity, and involvement in social activities. However, this implementation faces various challenges, including limited teacher understanding, lack of institutional support, and resistance from students. Therefore, this study recommends strengthening teacher training, providing institutional support, and innovating learning methods so that Qur'anic values can be implemented more effectively and sustainably in schools.